Pengembangan E-Modul Berbasis Model Pembelajaran Inkuiri Terbimbing Berbantuan Game untuk Meningkatkan hasil Belajar Kimia SMA - Meriyenti, Meriyenti; Efendi, Raimon; Estuhono, Estuhono (Universitas Negeri Padang, 2025)
This study was conducted in response to the low learning outcomes of Grade XI Chemistry students at SMAN 10 Tebo, which were attributed to limited learning media variation, low student engagement, and minimal use of interactive technology. The purpose of this research was to develop a guided inquiry-based e-module integrated with educational games to enhance students’ understanding of hydrocarbon compounds. The development process followed the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the e-module was assessed in terms of validity, practicality, and effectiveness. The research participants included a chemistry teacher and 11th-grade students from SMAN 10 Tebo. Data were collected through validation sheets, response questionnaires, and achievement tests. The e-module incorporated interactive components such as Wordwall-based educational games and Quizizz assessments to promote active learning. The findings revealed that the e-module was valid (Aiken’s V = 0.91), highly practical (teacher practicality = 97.73%; student practicality = 92.79%), and highly effective (average N-Gain = 0.75). Based on these results, the guided inquiry-based e-module integrated with educational games is recommended as a valid, practical, and effective tool to improve students’ chemistry learning outcomes, particularly on hydrocarbon materials.